THE INFLUENCE OF SELF-REGULATION AND PEER SUPPORT ON SUBJECTIVE WELL-BEING IN JUNIOR HIGH SCHOOL STUDENTS WHO ARE VICTIMS OF BULLYING - Karyoto, Karyoto; Suwarjo, Suwarjo; Eliasa, Eva Imania (Universitas Labuhanbatu, 2024)
The study aims to determine the effect of self-regulation and peer support on subjective well-being in junior high school students who are victims of bullying. This study uses a quantitative approach with a type of causality research through a survey method. The population of this study was junior high school students in Sorong Regency who had been victims of bullying whose number is not known for certain. The sample size was determined using the Cochran formula, obtaining a sample of 380 students. The data collection instrument used the subjective well-being scale, self-regulation scale, and peer support scale. While data analysis used prerequisite tests, namely the normality test using the Kolmogorov Smirnov test and probability plot, multicollinearity test, and heteroscedasticity test. Hypothesis testing used multiple regression analysis tests. Based on the research results, it shows that: (1) There is a positive and significant influence of self-regulation on subjective well-being in junior high school students who are victims of bullying with t = 8.267 (α = 0.000; α < 0.05), (2) There is a positive and significant influence of peer support on subjective well-being in junior high school students who are victims of bullying with t = 2.868 (α = 0.004; α <0.05), and (3) There is a positive and significant influence of self-regulation and peer support on subjective well-being in junior high school students who are victims of bullying with F = 48.486 (α = 0.000; α <0.05) . The results of the study indicate that self-regulation and peer support have a positive and significant influence on subjective well-being in students who are victims of bullying. The magnitude of the influence of self-regulation and peer support on subjective well-being in junior high school students who are victims of bullying is 0.20, which means that self-regulation and peer support influence subjective well-being in junior high school students who are victims of bullying by 20.5%, while the rest is influenced by other factors not discussed in the study.